Student-athletes with Disabilities Have the Right to Participate: Editor: Thomas H. Sawyer. Issue 2 (12th February 2016) - DeMartini, Anne
Abstract : The plaintiffs moved for a preliminary injunction against the enforcement of the Ohio High School Athletic Association instate residency requirement for student athletes, because it discriminated against their son on the basis of his disability by preventing him from participating in his high school sport program.